Inactivation of the Parietal Reach Region Causes Optic Ataxia, Impairing Reaches but Not Saccades - Hwang, Eun Jung (2012)
Lesions in human posterior parietal cortex can cause optic ataxia (OA), in which reaches but not saccades to visual objects are impaired, suggesting separate visuomotor pathways for the two effectors. In monkeys, one potentially crucial area for reach control is the parietal reach region (PRR), in which neurons respond preferentially during reach planning as compared to saccade planning. However, direct causal evidence linking the monkey PRR to the deficits observed in OA is missing. We thus inactivated part of the macaque PRR, in the medial wall of the intraparietal sulcus, and produced the hallmarks of OA, misreaching for peripheral targets but unimpaired saccades. Furthermore, reach errors were larger for the targets preferred by the neural population local to the injection site. These results demonstrate that PRR is causally involved in reach-specific visuomotor pathways, and reach goal disruption in PRR can be a neural basis of OA.